Cycling time trial is more altered in hypobaric than normobaric hypoxia - Saugy, J. J.; Rupp, T.; Faiss, R.; Lamon, A.; Bourdillon, N.; Millet, G. P. (Medicine & Science in Sports & Exercise, 2016)
Purpose: Slight physiological differences between acute exposure in normobaric hypoxia (NH) and hypobaric hypoxia (HH) have been reported. Taken together, these differences suggest different physiological responses to hypoxic exposure to a simulated altitude (NH) versus a terrestrial altitude (HH). For this purpose, in the present study, we aimed to directly compare the time-trial performance after acute hypoxia exposure (26 h, 3450 min) by the same subjects under three different conditions: NH, HH, and normobaric normoxia (NN). Based on all of the preceding studies examining the differences among these hypoxic conditions, we hypothesized greater performance impairment in HH than in NH.